2017
DOI: 10.1364/ol.42.003741
|View full text |Cite
|
Sign up to set email alerts
|

Observations from direct UV-written, non-hydrogen-loaded, thermally regenerated Bragg gratings in double-clad photosensitive fiber

Abstract: In this Letter, experimental evidence is provided for an enhanced thermal sensitivity for a double thermal regeneration feature in fiber Bragg gratings fabricated by direct ultraviolet (UV) writing. Here 47 gratings of varying fluence and wavelength were written along a double-clad, germanium-doped core fiber. Subsequently thermal processing without hydrogen loading the fiber was performed and thermal treatment was carried out in a pure oxygen environment. Thermal sensitivity for the double regeneration increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…This expands on previous work made by the group [2] and potentially permits harsh environment aerospace deployments to be realized.…”
Section: Introductionsupporting
confidence: 56%
“…This expands on previous work made by the group [2] and potentially permits harsh environment aerospace deployments to be realized.…”
Section: Introductionsupporting
confidence: 56%
“…Hence, the grating reflection increases at around 400°C. This grating can be seen as a transition from a Type I to Type In grating, which was previously believed to be a double regeneration [15]. Such transitions have been reported in the literature [11].…”
supporting
confidence: 60%
“…The strength of a regener ated FBG scales up with seed FBG reflectivity and RI modu lation [20]. The thermal regeneration of an FBG inscribed in double clad nonhydrogenated fiber using frequencydoubled argon-ion laser is also studied [23]. It is shown that the regen eration factor increased by a factor of 1.73 as the fluence increased from 19 kJ cm −2 to 44 kJ cm −2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal regeneration of an FBG inscribed in double clad nonhydrogenated fiber using frequencydoubled argon-ion laser is also studied [23]. It is shown that the regen eration factor increased by a factor of 1.73 as the fluence increased from 19 kJ cm −2 to 44 kJ cm −2 [23]. However, a comprehensive study on the role of UV fluence on thermal regeneration characteristics of FBGs written in hydrogenated fiber, and corresponding analysis, is lacking.…”
Section: Introductionmentioning
confidence: 99%